2019
DOI: 10.1386/cjcs_00004_1
|View full text |Cite
|
Sign up to set email alerts
|

The coverage of the international press in framing the Catalan sovereignty process: Analysis of ten leading EU and US newspapers 2010–17

Abstract: The Catalan sovereignty process has been a topic of interest in the mass media worldwide in recent years. We analysed nearly 900 stories, published between 10 June 2010 and 4 October 2017 by the main newspapers of France, Germany, Italy, the United Kingdom and the United States, for content in terms of genres, frames and journalistic sources. We also conducted in-depth interviews with the newspaper foreign correspondents to Spain. A main conclusion is that all the newspapers framed the sovereignty process as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Between 2010 and 2019 large-scale public demonstrations on the streets of Barcelona were a recurring feature of the Catalan secession movement. From 2010 onwards, support for the right to decide on secession grew rapidly in the region after Spain’s high court decided to block Catalonia’s new statue of autonomy first proposed in 2006 (Pont-Sorribes et al, 2019). In particular, the demonstration held on July 10th 2010 was significantly larger than previous events and was one of the largest in Spain’s post-transition period (Subirats & Vilaregut, 2012).…”
Section: The Political Context Of the Catalan Conflictmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2010 and 2019 large-scale public demonstrations on the streets of Barcelona were a recurring feature of the Catalan secession movement. From 2010 onwards, support for the right to decide on secession grew rapidly in the region after Spain’s high court decided to block Catalonia’s new statue of autonomy first proposed in 2006 (Pont-Sorribes et al, 2019). In particular, the demonstration held on July 10th 2010 was significantly larger than previous events and was one of the largest in Spain’s post-transition period (Subirats & Vilaregut, 2012).…”
Section: The Political Context Of the Catalan Conflictmentioning
confidence: 99%
“…In particular, the street demonstrations that have accompanied the political process have been widely studied (e.g., Alonso-Muñoz, 2014; Capdevila & Moragas-Fernández, 2019; Castelló, 2015; Gili et al, 2018; Moragas-Fernández & Capdevila, 2017; Palà Navarro, 2018; Xambó et al, 2014) while the secession process has also attracted interest from researchers examining the use of social media, its coverage in the national media, the strategies of the political parties, and the role played by television and radio (Algaba & Bellido-Pérez, 2019; Ballesteros, 2015; Guerrero-Solé, 2017; Martínez & Álvarez-Peralta, 2016; Monferrer & Bellido, 2018; Palà Navarro, 2020; Perales-García et al, 2019; Pont-Sorribes et al, 2018; Sampedro et al, 2021; San Cornelio & Gómez, 2019; Xicoy-Comas et al, 2017, 2020). Finally, research into the international repercussions of the process has been the object of several studies, especially devoted to the treatment given to the Catalan conflict in the international press (e.g., Dubois & Villeneuve-Siconnelly, 2019; Høeberg, 2014; Perales-García & Pont-Sorribes, 2018; Pont-Sorribes et al, 2019).…”
Section: Academic Literature On the Catalan Secession Processmentioning
confidence: 99%
“…The press coverage of Catalonia's independence aspirations has previously been discussed in various papers. For instance, Pont-Sorribes et al (2019) found that most stories in Europe and the USA contained specific predominant frames, including conflict and responsibility. The authors concluded that the media discourse in the international press was based on conflict and difference.…”
Section: Introductionmentioning
confidence: 99%
“…The large number of samples which we have read in order to carry out our research (901 press articles and 3.822 Twitter posts) makes this a methodical and rigorous study of how the traditional media (in this case printed) and the social networks (specifically Twitter) interpreted the events that occurred between October 1st and October 8th, 2017. This research does not focus exclusively on either the press (Vellón, 2020;Pont-Sorribes et al, 2019;Dubois & Villeneuve-Siconnelly, 2019;Perales-García & Pont-Sorribes, 2017;Cartes-Barroso, 2018;Dorado & Sixto-García, 2021;Xicoy et al, 2017;Irala-Hortal, 2020) or on social networks (Anderson, 2019;San Cornelio & Gómez Cruz, 2019;Carrasco et al, 2018;Hernández-Santaolalla & Sola-Morales, 2019;Gil Ramírez, 2019) as other previous studies have done, but instead includes both, in their textual and visual dimensions, which allowed us to establish diverse comparatives of the regional/national/international axes and/or the press and Twitter, which enriches the exploration of the discursive and communicative complexity which characterized the events of October 1st. As can be seen, this comparative approximation has been less frequently employed in the field of communication research in Spain (Pérez Curiel, 2020).…”
mentioning
confidence: 99%